Pengaruh Usability Aplikasi Transaksi Antar Bank (Studi Kasus: Fintech Payment) - Vivi Novika; Tuti Anggraini; M. Ikhsan Harahap (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
This research aims to test the level of usability in fintech payment applications. The type of research in this thesis is quantitative. The data used is primary data which was processed through distributing questionnaires with variable instruments using a Likert scale which was distributed to respondents totaling approximately 100 people. The research method in this thesis uses a quantitative method using the PACMAD (People At The Center of Mobile Application Development) usability model. The data analysis technique used is a data analysis test consisting of validity test, reliability test, classic assumption test consisting of normality test, multicollinearity test and heteroscedasticity test, and also using multiple linear analysis, which consists of F test, T test, and test the coefficient of determination (RÂ²) using the SPSS version 22 application to process the data. The results of this research show that the effectiveness aspect has a significant positive effect on the usability of fintech payment applications. The efficiency aspect has a significant positive effect on the usability of fintech payment applications. The Satisfaction aspect does not affect the usability of fintech payment applications. The Learnability aspect has a significant positive effect on the usability of fintech payment applications. The Memorability aspect does not affect the usability of fintech payment applications. The error aspect does not affect the usability of fintech payment applications. And the risk aspect has a significant positive effect on the usability of fintech payment applications.